Numerical analysis of laser-pulse transient ignition of oxygen/methane mixtures in rocket-like combustion chamber. (June 2019) - Gargiulo, G.; Ciottoli, P.P.; Martelli, E.; Malpica Galassi, R.; Valorani, M.
Abstract: This paper describes a numerical study of the laser-pulse ignition sequence occurring in the combustion chamber of the M3 facility at DLR-Lampoldshausen. Our methodological approach relies on a variable fidelity modeling of the main phenomena of interest. In-house tools are fed with spatially homogeneous, isochoric, forced ignition problems, to derive a simplified methane/oxygen kinetic mechanism. The kernel formation after the laser pulse energy deposition is firstly studied in a one-dimensional framework, so as to test the simplified kinetic mechanism ability to reproduce the ignition behavior. The kernel initiation is also simulated in a two-dimensional mixing layer, to assess the ability of the simplified mechanism to accurately describe both the kernel initiation and its spatial propagation. Both the one- and two-dimensional simulations are carried out by means of a wavelet-based CFD library. Next, a lumped analysis of the events connected with the ignition sequence is carried out by adopting a well-stirred reactor model for the M3 chamber. The numerical results are compared to experiments carried out by DLR-Lampoldshausen, and the discrepancies are discussed. Finally, the whole M3 geometry and ignition sequence are simulated by means of an Unsteady Reynolds-averaged Navier-Stokes (URANS) model under the axi-symmetric flow approximation. The URANS results are compared with the experimental data, showing that URANS axi-symmetric calculation are able to provide a rather accurate picture of the ignition transients. Nevertheless, some issues on the quantitative accuracy of the URANS predictions are found and discussed in detail. Highlights: The ignition transient complexity is dealt with a variable fidelity approach. Finite-rate kinetics is employed with a 15-species simplified mechanism. The WSR model agrees with experiments but fails to predict the pressure peak. 2D axi-symmetric URANS provides a rather detailed picture of the ignition events. URANS predicts larger-than-experiment chamber pressure peak value and growth rate.